The role of the masjid in disaster management: qualitative data specifically by informants based on their experiences - Utaberta, Nangkula; Md Esa, Intan Rahayu (American-Eurasian Network for Scientific Information, 2016)
The masjid is a religious institutions. The role of the masjid are considered as centre of community development since the time of the Prophet (pbuh). Masjid plays important role in enhancing the spirituality of the community at large and have their own spiritual values. In contemporary world, the role of masjid in the field of development received less attention and recognition. Similarly, the role and function of the mosque in disaster situations are overlooked because we only recognize the important functions when the natural disaster occurred. An assessment is made to see the potential of a masjid in disaster situations and also the efforts to explore and implement the functions and role of the masjid in responding to disasters. The main objective of this study was to assess and document the role and functions of the masjid in disaster management and relief of disasters in flood affected areas in the state. Assessment will be made through qualitative analysis in which the conclusions will be made based on the experiences of those experts involved in flood affected areas. The results of the evaluation is that, the masjid is seen as one of the most important centres in flood management in which it would indirectly become a major centre focused on post-flood management in Kelantan.